Antimycobacterial Activity and Brine Shrimp Toxicity of Wild Mushrooms Used by Communities in Southern Tanzania - Michael Qwarse*; Mainen Julius Moshi; Matobola Joel Mihale; Alphonce Ignace Marealle; Ramadhani Selemani Omari Nondo; Joseph Sempombe; Veronica Mugoyela (Iranian Society of Pharmacognosy, 2024)
Background and objectives: Several wild mushroom species occur in southern Tanzania and are used as food by the local tribes. Experience shows that some of them could contain phytochemical compounds with therapeutic potential for treating various diseases. This study aimed to evaluate wild mushrooms used by indigenous communities living near the Selous- Niassa corridor in Namtumbo district, in Southern Tanzania for safety and antimycobacterial activity. Methods: Wild mushroom samples were collected randomly during the wet season and extracted by cold maceration. Dried extracts were evaluated for safety using the brine shrimp lethality test and for antimycobacterial activity using a twofold microdilution method against non-pathogenic Mycobacterium madagascariense, Mycobacterium indicus pranii, and Mycobacterium aurum. Results: The mushroom extracts exhibited a good safety profile against brine shrimp larvae with LC50 values ranging from 20.28 µg/mL (moderately toxic) to 465.97 µg/mL (nontoxic). The extracts exhibited variable antimycobacterial activity against M. madagascariense, M. indicus pranii, and M. aurum with minimum inhibitory concentrations (MIC) between 0.78 and 12.5 mg/mL against M. madagascariense, 0.098 and 6.25 mg/mL against M. indicus pranii and 1.25 and 2.5 mg/mL against and M. aurum. Nineteen wild mushroom species (59.4%, n = 32) exhibited antimycobacterial activity against all three mycobacterial species used. Conclusion: Preliminary investigation has provided evidence that some of the mushrooms locally available are not toxic. Some of these mushrooms have the potential to yield antimicobacterial active compounds. Further studies to determine the therapeutic and nutritional value of these mushrooms are needed.